Formation of the calcium/poly(3-hexylthiophene) interface: Structure and energetics - Zhu, Junfa; Bebensee, Fabian; Hieringer, Wolfgang; Zhao, Wei; Baricuatro, J. H.; Farmer, Jason A.; Bai, Yun; Steinrück, Hans-Peter; Gottfried, Michael; Campbell, C. T. (Journal of the American Chemical Society, 2009)
The adsorption of Ca on poly(3-hexylthiophene) (P3HT) has been studied by adsorption microcalorimetry, atomic beam/surface scattering, X-ray photoelectron spectroscopy (XPS), low-energy He ion scattering spectroscopy (LEIS), and first-principles calculations. The sticking probability of Ca on P3HT is initially 0.35 and increases to almost unity by 5 ML. A very high initial heat of adsorption in the first 0.02 ML (625-500 kJ/mol) is attributed to the reaction of Ca with defect sites or residual contamination. Between 0.1 and 0.5 ML, there is a high and nearly constant heat of adsorption of 405 kJ/mol, which we ascribe to Ca reacting with subsurface sulfur atoms from the thiophene rings of the polymer. This is supported by the absence of LEIS signal for Ca and the shift of the S 2p XPS binding energy by -2.8 eV for reacted S atoms. The heat of adsorption decreases above 0.6 ML coverage, reaching the sublimation enthalpy of Ca, 178 kJ/mol, by 4 ML. This is attributed to the formation of Ca nanoparticles and eventually a continuous solid Ca film, on top of the polymer. LEIS and XPS measurements, which show only a slow increase of the signals related to solid Ca, support this model. Incoming Ca atoms are subject to a kinetic competition between diffusing into the polymer to react with subsurface thiophene units versus forming or adding to three-dimensional Ca clusters on the surface. At ∼1.6 ML Ca coverage, Ca atoms have similar probabilities for either process, with the former dominating at lower coverage. Ultimately about 1.6 ML of Ca (1.2 x 10 atoms/cm) reacts with S atoms, corresponding to a reacted depth of ∼3 nm, or nearly five monomerunit layers. Density-functional theory calculations confirm that the heat of reaction and the shift of the S 2p signal are consistent with Ca abstracting S from the thiophene rings to form small CaS clusters. © 2009 American Chemical Society.